Diseño de centro y plataforma logística de carga en Duitama-Boyacá como parte de una estrategia para mejorar el flujo de carga en la región (2021)
This degree work proposes the design of the cargo logistics platform for Duitama, whose main objective is to serve as a flow strategy and support to the transportation sector of Boyacá, from this research was obtained the characterization of the transportation sector of the region and identification of the demand for cargo transportation focusing on the products of greater supply and mobility having as central axis of the industrial corridor the city of Duitama. In the requirements analysis section of the logistics platform, the technical needs and strategic location that the platform must have are determined, based on logistics methodologies and parameters that determine its correct operation; to finally focus on the design and feasibility analysis of the structure from the plant design and analysis of costs and accounting flows of the investment.